2019
DOI: 10.1016/j.pocean.2019.03.003
|View full text |Cite|
|
Sign up to set email alerts
|

Variability and change in the west Antarctic Peninsula marine system: Research priorities and opportunities

Abstract: The west Antarctic Peninsula (WAP) region has undergone significant changes in temperature and seasonal ice dynamics since the mid-twentieth century, with strong impacts on the regional ecosystem, ocean chemistry and hydrographic properties. Changes to these long-term trends of warming and sea ice decline have been observed in the 21 st century, but their consequences for ocean physics, chemistry and the ecology of the high-productivity shelf ecosystem are yet to be fully established. The WAP shelf is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 366 publications
(510 reference statements)
5
119
0
5
Order By: Relevance
“…It may be that previous associations of cryptophytes with salinity were largely driven by collinearity between salinity and temperature. Alternatively, differences in species-specific responses to environmental variables could also be responsible for the variances observed (Henley et al 2019).…”
Section: Summer Phytoplankton Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that previous associations of cryptophytes with salinity were largely driven by collinearity between salinity and temperature. Alternatively, differences in species-specific responses to environmental variables could also be responsible for the variances observed (Henley et al 2019).…”
Section: Summer Phytoplankton Dynamicsmentioning
confidence: 99%
“…However, the physicochemical drivers behind community shifts towards flagellated phytoplankton remain unclear, likely due to the diversity among flagellated phytoplankton spanning different taxonomic groups and cell sizes, and each may interact differently with the physicochemical environment. Our current understanding of the drivers associated with the seasonal progression within the phytoplankton community (Henley et al 2019), particularly the pico-(≤ 3 µm) and nano-sized (> 3-20 µm) phytoplankton, limits our ability to accurately predict how polar marine systems will respond to future climate change with implications for food-web dynamics and the marine carbon cycle (e.g. Pinhassi et al 2004;Conan et al 2007;Christaki et al 2008;Obernosterer et al 2008;Agustí and Duarte 2013;Evans et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that although the phytoplankton community and events of Antarctic blooms are commonly dominated by diatoms, other taxa are also important components of the trophic web (Henley et al, 2019). Increases in cryptophytes and other flagellates have previously been reported (e.g., Phaeocystis antarctica and Gymnodiniales), as well as the substitution of diatoms for these flagellates in WAP, due to the influence of sea ice melt (Moline et al, 2004;Mendes et al, 2013;Lange et al, 2014;Mendes et al, 2017), as observed in the WAP sectors of the present study (Figure 3): sector 1 (Wasiłowska et al, 2015), sector 4 (Mendes et al, 2012(Mendes et al, , 2013, oceanic regions of sectors 5 (Mar de Weddell) and 6 (Passagem de Drake) (Mendes et al, 2012), as well as sectors 7 (Mendes et al, 2018), 9 (Gerlache Strait) (Mendes et al, 2017;Russo et al, 2018) and 11 (Arrigo et al, 2017).…”
Section: The Relationship Between Microphytoplankton Community Structmentioning
confidence: 99%
“…The WAP has been warming since at least the 1950s with increasing winter air temperature and precipitation (Kirchgäßner, ). During our study period, there was no trend in precipitation, and after decades of sea ice decline from 1970 to 2009 (most notably the ice season became shorter), sea ice began to rebuild along the WAP after reaching a local minimum in 2008–2009 (i.e., the annual ice season became longer post‐2008–2009) (Henley et al, ; Schofield et al, ). In general, to detect an ecologically relevant trend in phenological datasets it may be necessary to consider and evaluate environmental conditions over the same temporal scales.…”
Section: Discussionmentioning
confidence: 89%
“…We tested for a trend in the estimated Adélie penguin mean CID over time. It has been recently recognized that sea ice trends began leveling off or reversing along the WAP since about 2008–2009 when a local minimum in annual ice season duration was observed, after which there was an increase in the length of the annual ice season (Henley et al, ; Schofield et al, ), at least until ~2016. Therefore, using linear regression, we tested for trends in observed CIDs and predicted CIDs over time by assessing the time series before and after this local minimum.…”
Section: Methodsmentioning
confidence: 99%